Environmental impact food labels combining carbon, nitrogen, and water footprints. (May 2016) - Leach, Allison M.; Emery, Kyle A.; Gephart, Jessica; Davis, Kyle F.; Erisman, Jan Willem; Leip, Adrian; Pace, Michael L.; D'Odorico, Paolo; Carr, Joel; Noll, Laura Cattell; Castner, Elizabeth; Galloway, James N.
Highlights: Carbon, nitrogen, and water footprints demonstrate environmental impacts from food. Four environmental impact label designs are presented as models. Three footprint calculation methods provide diverse levels of detail for consumers. Governments, certifiers, grocers, and local farmers can use food labels. Labels could help consumers make food choices based on environmental impacts. Abstract: The environmental impact of the production and consumption of food is seldom depicted to consumers. The footprint of food products provides a means for consumers to compare environmental impacts across and within product groups. In this study we apply carbon, nitrogen, and water footprints in tandem and present food labels that could help inform consumers about the environmental impacts of individual food products. The footprint factors used in this study are specific to the United States, but the concept can be applied elsewhere. We propose three methods of footprint calculations: footprint weight, sustainability measures, and % daily value. We apply the three footprint calculation methods to four example labels (stars label, stoplight label, nutrition label add-on, and a detailed comparison label) that vary in design and the amount of detail provided. The stars label is simple and easily understood but provides minimal detail about the footprints. At the other end of the spectrum, the detailed comparison label gives context in relative terms (e.g., carbon emissions for equivalent distance driven) for the food product. Implementing environmental impact food labels requires additional understanding of how consumers use footprint labels, and label suitability may vary for government organizations, retail and local grocers, and farmers.